Bang! - Flake, Sharon G. (New York : Jump at the Sun/Hyperion Books for Children, 2005)
A teenage boy must face the harsh realities of inner city life, a disintegrating family, and destructive temptations as he struggles to find his identity as a young man.
Keywords: Violence -- Fiction; Family problems -- Fiction; Coming of age -- Fiction; African Americans -- Fiction; Inner cities -- Fiction; Violence -- Fiction; Family problems -- Fiction; Bildungsromans; African Americans -- Fiction; Inner cities -- Fiction; Urban fiction